Hybrid MDM-PDM Based Ro-FSO System for Broadband Services by Incorporating Donut Modes Under Diverse Weather Conditions - Chaudhary, Sushank; Wuttisittikulkij, Lunchakorn; Nebhen, Jamel; Tang, Xuan; Saadi, Muhammad; Al Otaibi, Sattam; Althobaiti, Ahmed; Sharma, Abhishek; Choudhary, Sunita (Frontiers in Physics, 2021)
High-speed data demand in sensitive locations has prompted new wireless technologies to grow in areas like hospitals for bio-sensor data transmission between doctors and patients. However, interference of electromagnetic spectrum or highly sensitive medical equipment in such locations can prevent radio waves which can further compromise the health of patients. Radio over Free Space Optics (Ro-FSO) can fulfil high-speed data demand in such locations without any such interference. However, the Ro-FSO performance is highly influenced by different adverse weather conditions, particularly haze and rainfall, which further cause attenuation in the transmission path of Ro-FSO systems. These atmospheric turbulences mainly affect the transmission link range of Ro-FSO systems. In this work, Ro-FSO system is designed by incorporating hybrid mode division multiplexing (MDM) and polarization division multiplexing (PDM) schemes to deliver four independent channels, each carrying 10 Gbps data upconverted to 40 GHz radio signal, over 3.4 km free space optical link operating under clear weather conditions. In addition to this, the proposed Ro-FSO link is subjected to different weather conditions, particularly partially hazy/rainy and dense fog/very rainy. The reported results indicate the achievement of acceptable bit error rate (BER≈10–3) for all channels up to 3400m FSO link under clear weather conditions, 1000m under partially haze/rain and 620 m under dense fog/heavy rain.